2019
DOI: 10.1111/jpy.12813
|View full text |Cite
|
Sign up to set email alerts
|

Size scaling of photophysiology and growth in four freshly isolated diatom species from Ryder Bay, western Antarctic peninsula

Abstract: Diatoms are one of the dominant groups in phytoplankton communities of the western Antarctic Peninsula ( WAP ). Although generally well‐studied, little is known about size dependent photophysiological responses in diatom bloom formation and succession. To increase this understanding, four Antarctic diatom species covering two orders of magnitude in cell size were isolated in northern Marguerite Bay ( WAP ). Fragilariopsis sp., Pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(238 reference statements)
0
6
0
Order By: Relevance
“…Mean values (±SD) are the average of four independent measurements. P. glacialis under similar conditions were consistent and around 0.3 day −1 (Gilstad and Sakshaug, 1990;Kulk et al, 2019). While reported maximum growth rate for pennate diatoms were around 0.2 day −1 and was mainly collected from Fragilariopsis cylindrus and Nitzschia frigida, two representative pennate diatoms of the polar regions (Hegseth, 1992;Juhl and Krembs, 2010;Aslam et al, 2012Aslam et al, , 2018.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Mean values (±SD) are the average of four independent measurements. P. glacialis under similar conditions were consistent and around 0.3 day −1 (Gilstad and Sakshaug, 1990;Kulk et al, 2019). While reported maximum growth rate for pennate diatoms were around 0.2 day −1 and was mainly collected from Fragilariopsis cylindrus and Nitzschia frigida, two representative pennate diatoms of the polar regions (Hegseth, 1992;Juhl and Krembs, 2010;Aslam et al, 2012Aslam et al, , 2018.…”
Section: Discussionmentioning
confidence: 58%
“…The saturating pulse was provided by a red-LED with a peak illumination at 655 nm and set at 7,000 µmol photons m −2 s −1 and lasted for 400 ms for all measurements (Yan et al, 2019). The maximum photochemical efficiency of PSII was calculated as mainly contributed by the centric diatoms and was slightly lower than the maximum growth rate of ice diatom isolates or communities under similar temperature, salinity and light conditions reported in previous studies (Gilstad and Sakshaug, 1990;Hegseth, 1992;Juhl and Krembs, 2010;Aslam et al, 2012Aslam et al, , 2018Olsen et al, 2017;Kulk et al, 2019). In those studies, the maximum growth rates of T. antarctica, T. nordenskioeldii, and FIGURE 7 | Abundances of rbcL (cDNA) normalized to the gene copy number (cDNA/DNA) during the incubation.…”
Section: Discussionmentioning
confidence: 97%
“…Organic compounds in glacier ice must be biologically synthesized by CO 2 fixation by phototrophs, i.e., the microeukaryotes Thalassiosira antarctica and Hydrurus foetidus identified in ROJ and MAC samples or chemolithotrophs such as Streptomyces [ 45 , 46 ]. In our research, we have also identified some aerobic CO oxidizers as Corynebacterium [ 47 ], especially in the eastern glaciers.…”
Section: Resultsmentioning
confidence: 99%
“…With this objective, we grew five ecologically relevant Arctic (or bipolar) diatom species under a range of limiting, saturating and supersaturating light typical of their respective habitats, and documented changes in their growth rates, photophysiology and carbon fixation capabilities. Most knowledge on Arctic diatom photoadaption at the moment is (i) inferred from correlation‐based field observations (Kvernvik et al, 2021; Lewis et al, 2019; Schuback et al, 2017), (ii) assembled from independent studies targeting diverse photoadaptative traits in different polar species [reviewed by Lacour et al (2017)] and/or (iii) extrapolated from laboratory studies in which most taxa occur only in Antarctic (Kulk et al, 2019; Petrou et al, 2011; Strzepek et al, 2019). However, we lack studies describing dose–response relationships between environmental factors and diverse species dominating distinct niches over seasonal dynamics required by production models and ecological theory.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways are usually more active under high light and provide photoprotection(Wagner et al, 2016), but not always, as for instance cyclic electron flow around PSI is constitutive in green organisms(Munekage et al, 2004), a pathway suspected of having an enhanced rate in F. cylindrus compared to temperate diatom counterparts(Goldman et al, 2015). Interestingly,Kulk et al (2019), described a 2.5-fold increase in electron requirement per C fixed under limiting growth light in two out of four Antarctic diatom species, including Fragilariopsis sp. Coinciding with F. cylindrus being the only species for which we observed decreasing α* under the lowest gE in this study.4.2 | Contrasts in C-specific productivity among species and depending upon growth light intensityData on C-specific 14 C-uptake also reflected a photoadaptation gradient, with the lowest P C M in sympagic N. frigida and maximal P C M in open-water C. neogracilis.…”
mentioning
confidence: 99%